Accelerating the discovery of new dielectric properties in polymer insulation - Du, Boxue, 1961- (Advances in computer and electrical engineering (ACEE) book series., 2017)
"This book includes many aspects of power system insulation, some of which are quite different from each other. It focuses on insulators in high-speed railway system which required new dielectric properties different from traditional power system, polymer insulation exposed to multi-field in HVDC power system provided clues for the discovery of new polymer materials, and other topics"--